1995
DOI: 10.1109/20.489767
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of the magnetic properties of SmCo/sub 5/:Nb/sub 0.33/Cr/sub 0.67/ nanocomposites using mechanical alloying

Abstract: Nanocomposite structures composed of ferromagnetic particles dispersed in a matrix are systems in which the magnetic properties can be tailored by varying the size and spacing of the ferromagnetic particles. Nanocompo$i~es of SmCos in a non-magnetic Nb0.dk8.67 matrix exhibit a wide variety of magnetic properties. SmCos powder is premilled prior to mechanical alloying. The premilliing results in a maximum coercivity of 16 kOe after 2 hours of milling, and an enhanced remanence ratio. Both features may be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…169,[257][258][259][260][261][262][263] Subsequent studies focused on Sm(Fe,X) 12 , 264 (Sm,Zr)Fe 3 , 265 Sm 2 -Fe 17 N x , [266][267][268] FeZr, 269 and CoNbB. 270 Similar structures optimized for high remanence and coercivity have been formed by in the SmCo family by mechanical alloying, 225,[271][272][273] and in sputtered SmCo/CoFe multilayers. 274 In 1991, Kneller and Hawig 275 suggested that anisotropy could be transmitted across hard and soft magnetic phases via exchange coupling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…169,[257][258][259][260][261][262][263] Subsequent studies focused on Sm(Fe,X) 12 , 264 (Sm,Zr)Fe 3 , 265 Sm 2 -Fe 17 N x , [266][267][268] FeZr, 269 and CoNbB. 270 Similar structures optimized for high remanence and coercivity have been formed by in the SmCo family by mechanical alloying, 225,[271][272][273] and in sputtered SmCo/CoFe multilayers. 274 In 1991, Kneller and Hawig 275 suggested that anisotropy could be transmitted across hard and soft magnetic phases via exchange coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The first experimental observations were in Nd 2 Fe 14 B compounds, which exhibited remanence ratios up to 0.9. ,− Subsequent studies focused on Sm(Fe,X) 12 , (Sm,Zr)Fe 3 , Sm 2 Fe 17 N x , FeZr, and CoNbB . Similar structures optimized for high remanence and coercivity have been formed by in the SmCo family by mechanical alloying, , and in sputtered SmCo/CoFe multilayers . In 1991, Kneller and Hawig suggested that anisotropy could be transmitted across hard and soft magnetic phases via exchange coupling.…”
Section: Resultsmentioning
confidence: 99%
“…Rare earth-transition metal ͑RE-TM͒ compounds with iron or cobalt as the TM constituent and one of the magnetic light REs, i.e., Pr, Nd, or Sm, as the RE constituent are especially well-suited for use as high-temperature, highperformance permanent magnets. [1][2][3][4][5][6][7][8][9][10][11][12] In the RE-TM intermetallic compounds, the RE unpaired 4f electrons provide the magnetocrystalline anisotropy, which is potentially much stronger than the shape anisotropy, whereas the TM 3d electrons provide most of the magnetization and determine the Curie temperature. The Sm-Co binary equilibrium phase diagram indicates seven intermetallic compounds ͑RE:TM ratios 2:17, 1:5, 2:7, 1:3, 1:2, 9:4, and 3:1͒ that are stable under standard atmospheric conditions.…”
mentioning
confidence: 99%
“…Composite materials with ferromagnetic properties have been since long fabricated by incorporating ferromagnetic materials as finely divided inclusions (like iron powders or fibers [2,4], barium ferrites [4], strontium particles [6], flakes of Fe-Cr [7], SmCo5 [8], iron nitride [9], iron oxide [10], CoFe [11] and ferrites [12,13]) into different non-magnetic metal matrices (Zn-22Al, Cu-ZnAl, Nb 0.33 Cr 0.67 , silver and copper). These soft magnetic powder-based composites (FPC), often fabricated by the established procedures of powder packing and ulterior densification by liquid infiltration with an appropriate matrix, were firstly developed aiming to replace some steel parts, subjected to time-varying magnetic fields, in electromagnetic devices of high power converter units and electric motors [1][2][3][4][5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%